Supervisi Akademik Kepala Sekolah Dasar untuk Meningkatkan Kinerja Guru di Masa Pandemi Covid-19 (Studi Kasus di SD 1 Prambatan Kidul Kudus Tahun 2020) - Sulistyani Sulistyani (Universitas PGRI Semarang, 2021)
This study aims to improve the teacher performance of SD 1 Prambatan Kidul Kudus during the Covid-19 pandemic in 2020. This research is a School Action Research (PTS) which was conducted in 2 cycles of academic supervision. Actions taken were in the form of strengthening and training in managing online learning. The research data included scores of academic supervision, interviews, and documentation. Scores of academic supervision were analyzed descriptively, while the results from interviews and documentation were used as supporting data. The overall average score of academic supervision before pandemic (Pre-Cycle) was 82,06%. The overall average score of academic supervision during pandemic in the Even Semester 2019/2020 (Cycle I) fell to 77,67%. The overall average score of academic supervision during pandemic in the Odd Semester 2020/2021 (Cycle II) increased to 80,72%. Thus, strengthening and training in managing online learning improved teacher performance during the Covid-19 pandemic in 2020.